The Model of Lanna Floating Lantern for the Preservation of Environment and Promotion of Cultural Tourism : A Case Study of the 2022 Lanna Floating Lantern Festival at Nong Bua Phra Chao Luang, Choeng Doi, Doi Saket, Chiang Mai - Suanchan, Veerasak; กอปรพร นุกูลคาม; Usavaporamitchai, Pesol; munlikawong, sikarint (RMUTL Journal of Socially Engaged Scholarship, 2023)
The Chiangmai Yi Peng and Loy Krathong festivals are celebrated in tandem every year. Choeng Doi Subdistrict office organizes the Yi Peng festival as an annual event with the floating lanterns as the main activity. The release of the floating lanterns into the sky is believed to cleanse oneself of bad luck. However, the lanterns often prove hazardous since they eventually fall back to the ground and cause some forms of damage to the environment. The authors and the Choeng Doi Subdistrict office, informed of the problems, see that it is beneficial to design the platform for the exhibition of Lanna lantern models. The lantern exhibition platform can help preserve the lantern tradition in such a way that it does not cause any effect to the environment. The platform is designed to show spatial relations of the lanterns in their arrangement, reduce the amounts of released lanterns, and promote cultural tourism. The research consists of three steps: design concepts, site survey, and building perspective models. The models recreate the atmosphere of lantern releasing with an aid from reflections on the water surface in the lake and the Doi Saket mountain range in the background. Perspectives and locations were set to take photographs: the bridge end, the skew angle of the bridge, and the river bank. Scientific principles were applied to create perspectives on the sizes of objects as viewed from a distance, the longer the distance the smaller the object appears. The sizes of the lanterns and light gradation were used to heighten the depth of distance to subjects. The exhibition was successful. It received praises on its concept from both online and local media. This shows that the exhibition can help to keep the tradition alive, and to promote cultural tourism at Nong Bua Phra Chao Luang Lake.